An unusual presentation of lacrimal gland dirofilariasis - Amit Sethi; Vani Puri; Natasha Dogra (Indian Journal of Ophthalmology, 2017)
Dirofilariasis is a helminthic infection caused by filarial parasite of the genus Dirofilaria. It is a common zoonotic disease mostly affecting canines and uncommon in humans. It is endemic to Mediterranean countries, with few reports from other parts of the world. The clinical forms in humans are pulmonary, subcutaneous, and ocular. Ocular involvement is rare. We report a case of lacrimal gland dirofilariasis, an unusual ocular presentation which masquerades as a lacrimal gland tumor. Ours would be the third reported case in the world and first in India. This case was managed with excision of the lacrimal gland mass. Postoperatively the patient recovered completely and there has been no recurrence in the 1-year follow-up.